Progesterone improves the number and quality of hormone induced Fowler toad (Bufo fowleri) oocytes - Li Hong; Browne Robert K; Seratt Jessica; Kouba Andrew (BMC, 2006)
Abstract Combinations of progesterone, lutenizing hormone releasing hormone analogue (LHRHa), human chorionic gonadotrophin (hCG), and the dopamine-2 (DA2) receptor antagonist 1-[1-[4,4-bis(4-Fluorophenyl)butyl]-4-piperidinyl]-1,3-dihydro-2H-benzimidazol-2-one (Pimozide; Orap) were tested for improvement of spawning rates, oocyte numbers, fertilization and neurulation rates of the Fowler toad (Bufo fowleri). Only treatments combined with progesterone produced large numbers of oocytes. The best treatment on oocyte numbers, neurulation rates, and the number of neurulas was with 5 mg progesterone, 20 mic.g LHRHa, and 0.25 mg Pimozide. Progesterone (5 mg) with 60 mic.g LHRHa gave high spawning rates, oocyte numbers, and fertilization rates but neurulation rates were low. Progesterone alone in high repeated doses did not result in ovulation. High doses of LHRHa (60 mic.g) with hCG, progesterone, and Pimozide gave the greatest number of toads spawning, however, they resulted in low oocyte numbers, fertilization and neurulation rates. A low dose of LHRHa (4 mic.g) with hCG, or hCG alone as a second administration, and progesterone with Pimozide produced few good quality oocytes. Toads were given normal ovulatory doses of hormones 24 or 48 hrs after their initial dose, but these resulted in low oocyte numbers followed by poor fertilization. Overall, these results suggest that progesterone with a dose between 20 mic.g and 60 mic.g of LHRHa may be optimal for the induction of ovulation in these toads. Moreover, Pimozide can supplement low doses of LHRHa but not replace it.